Organizational learning in fast-changing environments and decision-making processes: a literature review - Fernández, Rafael (2018)
This paper reviews recent literature on organizational learning in market dynamics. It also explores if there has been a significant research on the impact of organizational learning and its dynamic capabilities on the decision-making process at an organizational level.